Analisis Kesulitan Siswa dalam Menyelesaikan Soal Cerita Bilangan Pecahan (LPPM UKI Toraja, 2023)
This research was carried out with the aim of knowing the causes of difficulties in solving fractional word problems in grade IV students. The approach used in this study is a qualitative approach with a qualitative description research type. The subjects of this study were teachers and 3 students at UPT SDN 1 Bittuang for the 2022/2023 academic year. Data collection techniques using observation, tests, interviews, and documentation. The data analysis technique used is the data reduction stage, the data presentation stage, and the conclusion drawing stage. The results of the study showed that the difficulty of solving fractional word problems in fourth grade students of UPT SDN 1 Bittuang consisted of three components, namely (1) difficulty solving problems in word problems such as lack of understanding of fractional word problems, not writing down what was known and asked to word problems, lack of accuracy in reading, and mistakes in mastering fraction material. (2) difficulty understanding the concept of fractions such as students having difficulty writing the numerator and denominator, unable to distinguish between the numerator and denominator, (3) and difficulties in arithmetic skills such as adding the numerator with the numerator, and the denominator with the denominator, making mistakes in changing mixed fractions into ordinary fractional numbers, miscalculations in addition operations, and not carrying out the calculation process.